Vicinal disubstitution of alkyl C–X synthons via alkene radical cation generation - Yufei Zhang; Tamal Das; Zi Xuan; Mrinmoy Das; Hammed O. Bisiriyu; Alon Nudler; Ben D. Parasch; Matthew D. Resmini; Aubrey E. Graham; David F. Watson; Jennifer S. Hirschi; Patricia Z. Musacchio (Science, 2026)
In organic chemistry, functionalization of two adjacent carbons often starts from alkenes or already disubstituted precursors. Herein, we report an exergonic activation mode that directly generates alkene radical cation intermediates from monofunctional C(sp 3 )–X handles through a photoredox-triggered hydrogen-atom abstraction (HAT) and spin-center shift (SCS) process. Computations show that electron delocalization and a network of hydrogen-bonding solvent molecules facilitate a concerted [HAT+SCS] mechanism. The catalytic platform was used to design a transfer of electrophilic reactivity (C–X) from one carbon to another, which we refer to as electrophilic shuttling. Thus, two nucleophiles can be used in the construction of 1,2-difunctionalization adducts from homobenzylic C–X synthons, delivering bisazole architectures and demonstrating compatibility with other nucleophile classes. A suite of transformations is developed that departs from conventional synthetic logic, for which alkyl C–X scaffolds are confined to single-site substitutions, now transforming them into nonintuitive precursors for building vicinal complexity.